2020
DOI: 10.1111/nmo.13929
|View full text |Cite
|
Sign up to set email alerts
|

Straight leg raise metrics on high‐resolution manometry associate with esophageal reflux burden

Abstract: Background: Straight leg raise (SLR) is a provocative maneuver that assesses esophagogastric junction (EGJ) barrier function during high-resolution manometry (HRM). We evaluated the value of SLR in symptomatic reflux patients undergoing ambulatory reflux monitoring. Methods: Adult patients being evaluated for reflux symptoms with esophageal physiologic testing off antisecretory therapy over a 12 month period were studied. Demographics, clinical presentation, HRM studies, and reflux monitoring studies were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…With the advent of HRM and the recognition that the CD is a crucial component of the EGJ barrier, there has been a better overall understanding of GERD pathophysiology. Rogers et al 28 first demonstrated a significant association between SLR and esophageal acid exposure time. However, strong evidence in terms of thresholds and modalities to establish a reproducible pressure increase is still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of HRM and the recognition that the CD is a crucial component of the EGJ barrier, there has been a better overall understanding of GERD pathophysiology. Rogers et al 28 first demonstrated a significant association between SLR and esophageal acid exposure time. However, strong evidence in terms of thresholds and modalities to establish a reproducible pressure increase is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…IAP increase became significant only in patients with severe LES alterations 1981 DeMeester et al 18 Importance of phrenoesophageal ligament insertion to provide competency during IAP increase 1982 Joelsson et al 19 Abnormal esophageal acid exposure on 24-h pH monitoring correlated to either an anatomic or functional LES dysfunction or a defective pump action of esophageal body 1986 Bonavina et al 20 Mixed clinical and in vitro study. Higher prevalence of abnormal 24-h pH test in patients with defective sphincter 1989 Mittal et al 21 Introduction of the 2-sphincter hypothesis: LES and CD are distinct sphincters that operate in synergy 1990 Mittal et al 22 Electromyography and atropine infusion in 15 healthy subjects showed diaphragmatic activation during IAP increase 1993 Klein et al 23 Demonstration of a high-pressure zone at the thoracoabdominal junction after esophagectomy reflecting the pinchcock effect of the CD 2011 Kwiatek et al 24 3-dimensional HRM study on CD contribution to competence of the EGJ 2013 Louie et al 25 Hiatal closure contributes more to restore LES pressure 2015 Lee and McColl 26 Obesity and waist belt contribute to reflux through disruption of EGJ and IAP increase 2017 Mitchell et al 27 Impaired clearance might be induced or worsened by increased high IAP, especially after meals 2020 Rogers et al 28 First use of straight leg raise maneuver with HRM, significant association between increased esophageal pressure during leg raise and AET 2020 Stefanova et al 29 Intraoperative EndoFLIP study in 100 patients who underwent Nissen, Toupet, or magnetic sphincter augmentation. Diaphragmatic repair and LES intra-abdominal relocation have greater effect on competency than sphincter augmentation 2021 Siboni et al 30 Hiatoplasty contribution to EGJ barrier function after magnetic sphincter augmentation 2021 Gysen et al 31 Introduction of gastrosphincteric pressure gradient to differentiate rumination from GERD patients 2021 Attaar et al 32 Intraoperative EndoFLIP study in 97 patients.…”
Section: Pressure Responsementioning
confidence: 99%
“… 7 In addition to a structurally deficient barrier, EGJ motor abnormalities consist of a hypotensive EGJ and transient LES relaxations, the latter being the most common in GERD. Another study demonstrated that an increase in peak intra-esophageal pressure ≥ 100% during SLR was associated with elevated AET in GERD patients, particularly those with type 1 EGJ morphology, 15 suggesting that physiological stress of the EGJ barrier using SLR may predict which patients are most susceptible to reflux events.…”
Section: Discussionmentioning
confidence: 99%
“… 11 - 14 Rogers et al 14 recently demonstrated that measurement of trans-EGJ pressure gradient during SLR can assess integrity of the EGJ barrier, and suggested that analysis of intra-esophageal pressure gradients during SLR can provide adjunctive evidence of pathologic GERD. 15 However, the clinical impact of transient SLR induced hiatal separation on esophageal acid burden remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, real-world clinical practice is not totally respectful of these guidelines [2]. More recently, provocative tests, including multiple rapid swallows, rapid drink challenge, solid meal swallows and straight leg raise maneuver have been added to improve the accuracy of HRM [3][4][5][6]. Variations in methodology among institutions may affect the intrinsically complex relationship between symptoms and HRM metrics and, indirectly, the reliability of the test [7].…”
Section: Introductionmentioning
confidence: 99%